2020
DOI: 10.1037/aap0000171
|View full text |Cite
|
Sign up to set email alerts
|

“I push through and stick with it”: Exploring resilience among Filipino American adults.

Abstract: Filipino Americans are the 3rd largest Asian subpopulation in the United States and have had a complex history regarding identity within the Asian American population due to Spanish and American colonization and immigration patterns to the United States (U.S. Census Bureau, 2017). This may account for unique psychological impacts on Filipino Americans that are often overlooked (David, 2013;Nadal, 2011). Limited research has examined resilience within Filipino Americans, yet existing studies have looked at over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Despite all of these challenges, most Latinx undergraduates seem to be persevering (Chavez, 2020; Douglas-Gabriel et al, 2021). Resilience, or the process and outcome of successfully adapting to difficult or challenging life experiences, especially through mental, emotional, and behavioral flexibility and adjustment to external and internal demands (Masten et al, 2009), has been found to characterize many Latinx students (Hufana & Morgan Consoli, 2020; Morgan Consoli et al, 2014, 2015; Morgan-Consoli et al, 2020). Yet, there has been little research in this area illuminating exactly how students are overcoming adversities or the nuanced picture of their day-to-day experiences during this particular time period.…”
mentioning
confidence: 99%
“…Despite all of these challenges, most Latinx undergraduates seem to be persevering (Chavez, 2020; Douglas-Gabriel et al, 2021). Resilience, or the process and outcome of successfully adapting to difficult or challenging life experiences, especially through mental, emotional, and behavioral flexibility and adjustment to external and internal demands (Masten et al, 2009), has been found to characterize many Latinx students (Hufana & Morgan Consoli, 2020; Morgan Consoli et al, 2014, 2015; Morgan-Consoli et al, 2020). Yet, there has been little research in this area illuminating exactly how students are overcoming adversities or the nuanced picture of their day-to-day experiences during this particular time period.…”
mentioning
confidence: 99%
“…Scholars have discussed the importance of taking into account the colonial context of the Filipina/o/x diaspora and colonial mentality to get a deeper understanding of the resettlement journey and experience (Aguila, 2015;Aguilar, 2015;Buenavista, 2010;David & Nadal, 2013;Ferrera, 2016;Haufana &Consoli, 2020 andKelly, 2015). Aguila (2015) specifically mentions that "for contemporary Filipinos, identity formation may involve a continuing resistance against colonialism now set amid the diaspora in the digital age" (p. 56).…”
Section: Colonial Context Of the Filipina/o/x Diaspora And Colonial M...mentioning
confidence: 99%
“…Two subdimensions of enculturation are interpersonal norms and conservatism (del Prado & Church, 2010). Enculturation has had negative effects on Asian Americans, including Filipino Americans (David et al, 2017;Hufana & Morgan Consoli, 2020;Rodriguez-Operana et al, 2017;Tuason et al, 2007). Higher social anxiety, more daily uncertainty, and lower feelings of competence were found among Asian Americans who held more closely to their culture of origin (Lee & Church, 2017).…”
Section: Cultural Adherence and Assertivenessmentioning
confidence: 99%
“…The population of Filipino Americans in the United States has reached four million and represents the third largest Asian group in the country (U.S. Census Bureau, 2019); there is a growing need for continued study and examination of the Filipino American experience. The conflict between Filipino and Western values drives the positive and negative experiences of daily life in Filipino Americans (David et al, 2017;Hufana & Morgan Consoli, 2020;Rodriguez-Operana et al, 2017;Tuason et al, 2007). One negative experience is the glass ceiling for Asians, also called the bamboo ceiling, a concept that describes the challenge Asian Americans face as they attempt to advance in the workplace (Chin, 2016;Hyun, 2005;Yu, 2020).…”
Section: Introductionmentioning
confidence: 99%